First description of immature stages of Gastropini, Gastrops willistoni Cresson (Diptera: Ephydridae) preying on eggs in a foam nest of Leptodactylus knudseni Heyer (Anura: Leptodactylidae) in Central Amazon - Camargo, Alexssandro; de Souza, Franciele Cristina; Zatwarnicki, Tadeusz (Zootaxa, 2020)
The third instar larva and puparium of Gastrops willistoni Cresson (Diptera: Ephydridae), preying on eggs in a foam nest of Leptodactylus knudseni Heyer (Anura: Leptodactylidae), in a central Amazonian dryland forest (Brazil) are described for the first time. The fusiform larva has a short breathing tube, its anterior spiracles are fan-shaped and posterior spiracles with three spircular openings. Pupa is ovoid with a broad anterior margin and bifurcate posterior tip. The taxonomic relationship of the frog egg predators, Gastrops Williston and Typopsilopa Cresson, are discussed.